2020
DOI: 10.1371/journal.pone.0230489
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-based versus population-based surveillance of antimicrobial resistance to inform empirical treatment for suspected urinary tract infection in Indonesia

Abstract: Surveillance of antimicrobial resistance (AMR) enables monitoring of trends in AMR prevalence. WHO recommends laboratory-based surveillance to obtain actionable AMR data at local or national level. However, laboratory-based surveillance may lead to overestimation of the prevalence of AMR due to bias. The objective of this study is to assess the difference in resistance prevalence between laboratory-based and population-based surveillance (PBS) among uropathogens in Indonesia. We included all urine samples subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
(15 reference statements)
1
12
0
Order By: Relevance
“…In a study from the United States in 2017 across both community and hospital E. coli isolates, AMR prevalence was very low, with maximum resistance observed for cotrimoxazole (32%), while carbapenems had 100 percent sensitivity (Table 5 ) [ 25 ]. Our analysis shows that the prevalence of AMR is alarmingly high in the developing countries as compared to developed nations in concurrence with other authors [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a study from the United States in 2017 across both community and hospital E. coli isolates, AMR prevalence was very low, with maximum resistance observed for cotrimoxazole (32%), while carbapenems had 100 percent sensitivity (Table 5 ) [ 25 ]. Our analysis shows that the prevalence of AMR is alarmingly high in the developing countries as compared to developed nations in concurrence with other authors [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…World Health Organization's global plan of action on AMR has stressed AMR surveillance across nations as an important strategy for reducing AMR [ 9 ]. Also, it has been shown that the emergence of AMR is proportionately more in the low- and middle-income countries [ 8 , 10 ]. This warrants continuous reporting and surveillance of the emergence of AMR among the uropathogens across regions and nations.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations propagate into our prevalence estimates, and they should thus be interpreted as an approximation of the true prevalence in a country. Future unbiased surveillance will likely require novel approaches, e.g., population-based surveillance ( 33 , 34 ), for which the necessary resources and infrastructure are not yet in place. Our predictive framework provides a means to support the prioritization of investments required for this.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, UTI incidence is around 180,000 new cases per year (Sugianli et al 2020). Escherichia coli is the most dominant pathogen acquired nosocomially (Ejrnaes 2011).…”
Section: Introductionmentioning
confidence: 99%